Tsunami Modeling Using DEMNAS and DEM Data from UAV Surveys for Planning Evacuation Routes on Samas Coast, Bantul Regency - Sihombing, Sulpisius; Sudarmaji; Sunardi, Bambang; Darmawan, Herlan (Journal of Geoscience, Engineering, Environment, and Technology, 2024)
The interaction between the Indo-Australian plate and the Eurasian plate exerts significant influence on seismic activities within the southern seas of Java Island, with potential repercussions extending to the triggering of tsunamis. Given the densely populated nature of this area, especially along the southern region of Yogyakarta Province, the coast of Samas Beach and its surroundings, mitigation efforts are needed to reduce the potential loss of life caused by tsunamis. One of the mitigation efforts is making a tsunami model which can be done using the help of DEMNAS and DEM topographical data from unmanned aerial vehicle (UAV) photogrammetry. The COMCOT software is a tool used in modeling tsunamis based on a numerical model of the shallow water equation that processes tsunami generator parameters and DEM data into an accurate tsunami model. The modeling results show that the tsunami waves will reach the Samas coast in the 38th minute after the occurrence of the earthquake. The maximum height of the tsunami inundation obtained using DEMNAS data was 21.72 m while using the UAV-DEM it was obtained 23.34 m. Comparison of modeling using DEMNAS and UAV-DEM data shows that image data collection using UAV has good resolution and has high accuracy so that it is able to produce a tsunami model that better shows the propagation of a tsunami in the actual field. The location used as a temporary/final evacuation site is Tegalsari Elementary School because of its strategic location and in tsunami modeling, this location is in the very low risk zone.